2021
DOI: 10.1177/25158414211009095
|View full text |Cite
|
Sign up to set email alerts
|

Complications and visual outcome of sutureless, scleral fixated intraocular lens in cases with traumatic aphakia

Abstract: Purpose: The aim of this study is to describe the complications and outcome of sutureless scleral fixated intraocular lens (SFIOL) implantation in traumatic aphakia. Setting: The study was conducted in a tertiary eye care centre in South India. Design: The study involved a retrospective data analysis. Methods: Medical records of cases with traumatic aphakia who had undergone sutureless SFIOL implantation in the last 2 years were included in the study. Data on intraoperative and postoperative complications and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It occurred in 15% sutured and 14 % in sutureless SFIOL. In a study by Deb A et al 19 Transient corneal edema was 17% which was similar to our study. Previous studies have shown corneal edema to be around 10% after scleral fixated intraocular lens.…”
Section: Discussionsupporting
confidence: 92%
“…It occurred in 15% sutured and 14 % in sutureless SFIOL. In a study by Deb A et al 19 Transient corneal edema was 17% which was similar to our study. Previous studies have shown corneal edema to be around 10% after scleral fixated intraocular lens.…”
Section: Discussionsupporting
confidence: 92%
“…Various intra-operative and post-operative complications have been reported in many studies following SFIOL implantation. [ 9 10 11 12 13 ] We observed that the anterior chamber was more stable during maneuvers in cases where pars plana infusion was established. To avoid anterior chamber distortion while operating using an anterior chamber maintainer, we recommend that the infusion be directed opposite to the main entry wound.…”
Section: Discussionmentioning
confidence: 84%
“…The HS technique is a time-tested method performed by surgeons all over the world since 2007. [ 9 ] The XNIT technique is a relatively newer concept introduced by our team in 2017 to minimize the most challenging intra-ocular maneuvers. [ 6 ] The results of our retrospective study show that both the HS and XNIT techniques achieved similar visual outcomes at 3 months with minimal complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…A thorough anterior vitrectomy is then performed through the PPV and side ports (figure 2C). A rigid three-piece IOL is subsequently implanted using modified extraocular needle-guided haptic insertion technique 7 (figure 2D).…”
Section: Descriptionmentioning
confidence: 99%